2010
DOI: 10.1098/rspb.2010.1680
|View full text |Cite
|
Sign up to set email alerts
|

Predation selects for increased immune function in male damselflies,Calopteryx splendens

Abstract: Predation selects for numerous traits in many animal species, with sick or parasitized prey often being at high risk. When challenged by parasites and pathogens, prey with poor immune functions are thus likely to be at a selective disadvantage. We tested the hypothesis that predation by birds selects for increased immune function in a wild population of male damselflies Calopteryx splendens, while controlling for a trait known to be under selection by bird predation, dark wing-spots. We found that selection on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 65 publications
1
15
1
Order By: Relevance
“…For example, potential biases might result from variation in the relative proportions of fore- and hindwings that could be retrieved. This may explain the discrepancy with the study of Rantala et al (2011), where no evidence for selection on wing size could be found when relating predation risk to hindwing length.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…For example, potential biases might result from variation in the relative proportions of fore- and hindwings that could be retrieved. This may explain the discrepancy with the study of Rantala et al (2011), where no evidence for selection on wing size could be found when relating predation risk to hindwing length.…”
Section: Discussioncontrasting
confidence: 90%
“…While there seems to be little or no evidence that wing morphology plays a role in RHP, it has previously been shown that several wing characteristics affect predation probabilities (Svensson and Friberg 2007; Rantala et al 2011). Specifically for C. virgo , stabilizing selection has been detected on both wing width and wing length such that males with intermediate values for both traits had a better chance of surviving predatory attacks by white wagtails ( Motacilla alba ) (Svensson and Friberg 2007).…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that under a manipulated high predation risk, damselflies increased their mass less during the maturation period (96). Studies showed that consumptive predation may shift phenotypic distributions of several traits, including immune traits (76) and sexually selected traits such as body size and wing spot size (105). This indicates that both nonconsumptive and consumptive predation changes the adult phenotype and therefore is expected to indirectly shape fitness components such as life span, mating success, and fecundity.…”
Section: Effects Of Environmental Conditions At the Adult Stagementioning
confidence: 96%
“…The ability to defend and recover quickly from infections is clearly vital for survival and reproductive success, and previous studies have indicated that the melanization response is particularly important in this context (Rantala et al. 2010; Rantala et al. 2011; Kaunisto et al.…”
Section: Resultsmentioning
confidence: 99%